Does adding fibre to a low energy, high carbohydrate, low fat diet confer any benefit to the management of newly diagnosed overweight type II diabetics?. Issue 6630 (23rd April 1988) - Beattie, V A; Edwards, C A; Hosker, J P; Cullen, D R; Ward, J D; Read, N W
Abstract : The effect of supplementing a low energy (roughly 5·0 MJ), high carbohydrate (180 g), low fat (roughly 25 g) diet with 10-15 g of either cereal fibre or guar gum was investigated in 24 newly diagnosed overweight non-insulin-dependent (type II) diabetics. The patients were divided into three treatment groups: one received a low fibre control diet throughout the study period of 20 weeks and the other received two supplements of cereal fibre and guar gum in a crossover manner. The nutrient content of the diets was kept constant throughout. Though patients taking the low fibre diet showed a smaller reduction in fasting plasma glucose concentrations over the first eight weeks than patients taking a high fibre diet, this difference was not evident at the end of 20 weeks; reductions in weight and glycated haemoglobin values were similar for each dietary regimen throughout the trial. There was little evidence that supplementing a low energy, high carbohydrate diet with fibre confers any therapeutic benefit to type II diabetics and no evidence that taking fibre as viscous polysaccharides is any more beneficial to overweight diabetics than taking a similar fibre supplement as cereal. On the contrary, guar gum caused more abdominal discomfort and flatulence than the other diets.